2014
DOI: 10.1186/1471-2156-15-s1-s7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing of transgenic poplar (Populus × euramericana 'Guariento') expressing multiple resistance genes

Abstract: BackgroundTransgenic poplar (Populus × euramericana 'Guariento') plants harboring five exogenous, stress-related genes exhibit increased tolerance to multiple stresses including drought, salt, waterlogging, and insect feeding, but the complex mechanisms underlying stress tolerance in these plants have not been elucidated. Here, we analyzed the differences in the transcriptomes of the transgenic poplar line D5-20 and the non-transgenic line D5-0 using high-throughput transcriptome sequencing techniques and eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 91 publications
0
15
0
1
Order By: Relevance
“…The few differences (Fig. 5) might be caused by differential expression of the transferred exogenous stress response genes, which affect different but related metabolic pathways (Zhang et al 2014). Additionally, we documented reduced numbers of Chloroflexi in the soils from rhizospheres of the planted poplars (transgenic poplars and wild-type poplars) compared with the uncultivated soil rhizosphere.…”
Section: Discussionmentioning
confidence: 66%
“…The few differences (Fig. 5) might be caused by differential expression of the transferred exogenous stress response genes, which affect different but related metabolic pathways (Zhang et al 2014). Additionally, we documented reduced numbers of Chloroflexi in the soils from rhizospheres of the planted poplars (transgenic poplars and wild-type poplars) compared with the uncultivated soil rhizosphere.…”
Section: Discussionmentioning
confidence: 66%
“…Despite the relative ease of obtaining transcriptomes, compared to complete genomes, there are relatively few published transcriptomes for tephritid species from next generation sequencing. Transcriptomes have been reported comparing wild and mass-reared medfly [ 87 ], adults and different developmental stages of B. dorsalis [ 88 , 89 ], pooled life stages of B. oleae [ 90 ] and sexed preblastoderm embryos of B. jarvisi [ 91 ]. Kumaran et al .…”
Section: Genome and Transcriptome Analysesmentioning
confidence: 99%
“…These changes also trigger the synthesis of specific biomolecules that cause a series of complex physiological and metamorphic alterations[ 23 26 ]. It has been suggested that stress-responsive genes can be more or less classified into two major categories based on their regulator molecules, the functions of their products, or their effector molecules[ 27 29 ]. The first group of molecules plays a direct role in abiotic stress tolerance, protect cells against damage, and sustain cell viability.…”
Section: Introductionmentioning
confidence: 99%